EFFECT OF BORDER CLOSURE ON THE BUSINESS ACTIVITIES OF BORDER COMMUNITIES IN NIGERIA (ABUJA JOURNAL OF BUSINESS AND MANAGEMENT, 2024)
This study investigated the impact of border closures on the business activities of border communities in Nigeria, specifically focusing on the effects on small businesses in Idiroko and Seme. Employing a descriptive research design, the study used purposive sampling to collect data from the 60 small business owners in these areas, with convenience and simple random sampling methods to select the respondents. Data were analyzed using inferential and descriptive statistics, as well as multiple regression analysis, with a 5% significance level to test the study's hypotheses. The results indicated that border closures significantly affect the recreation and entertainment sectors of the hospitality industry in border communities. The study concludes that border closures significantly affect the recreation and entertainment sectors of the hospitality industry in border communities. It is recommended that Hospitality businesses in border communities should diversify their services to reduce dependence on cross-border traffic. By expanding offerings to include virtual events or local community engagement activities, businesses can maintain revenue streams even during border closures.